Promoting Policy Reforms for Effective Transport Services in COMESA Countries - World Bank (Washington, DC, 2012)
Market for Eastern and Southern Africa (COMESA) has been promoting reforms to help regional integration for effective transport services. The study indicated the need for better traffic management, in general, and, specifically, to face up to the growing congestion problem in the capital cities. Roads in major cities have been neglected, therefore each country must include maintenance and management of urban roads in its transport strategy. In many of the countries, improved access was a major issue. A high percentage of the study area's population lacks modern road transport. Ethiopia, for example, has one of the lowest road densities in the world. Only 20 percent of its area is within 10 km of an all-weather road, and about 30 percent within the same distance of any kind of rural road. Nearly 90 percent of the population is rural and 85 percent employed in agriculture, but nearly three-quarters of all farms are more than a half-day's walk from an all-weather road. This dearth of roads is clearly a major economic and social constraint.